Catalytic partial oxidation of n-octane and iso-octane: Experimental and modeling results. (28th September 2017) - Carrera, Andrea; Pelucchi, Matteo; Stagni, Alessandro; Beretta, Alessandra; Groppi, Gianpiero
Abstract: The Catalytic Partial Oxidation (CPO) of two octane isomers, 2, 2, 4-trimethyl pentane (iso-octane) and n-octane, chosen as representative of gasoline is investigated by means of adiabatic tests and mathematical modeling. CPO experiments were carried out in a lab scale auto-thermal reformer with honeycomb monolith catalysts (2% Rh/α-Al2 O3 ), equipped with probes for spatially resolved measurements of temperature and concentration. Tests were performed with about 50% N2 dilution to prevent risks of deactivation due to catalyst over temperature. The CPO of the two isomers follows similar reaction pathways, which mainly consist of the exothermic combustion reaction and the endothermic steam reforming. This results in a close similarity of the concentration profiles of the main species and of the temperature profiles obtained with the two isomers. On the other hand, gas phase reactions proceed to a different extent and bring about a different distribution of thermal cracking products, iso-octane being more reactive and selective to iso-butylene and propene, while n-octane being selective to ethylene. Coke formation was observed upon adiabatic tests which was responsible for partial deactivation of the reforming zone of the catalyst. Post mortem TPO tests show that n-octane exhibits a higher tendency to coke deposition than iso-octane in the adopted CPO conditions. Thermodynamic and modeling calculations show that the risk of coking can be reduced by using exhaust gas recycling instead of N2 to dilute the reactants. Highlights: Catalytic partial oxidation of iso-octane and n-octane is addressed by spacy resolved measurements. C8 isomers behave similarly in adiabatic tests since kinetic differences are masked by mass transfer. Cracking products form in the gas phase and are consumed by catalytic steam reforming. Reactants dilution with N2 favors coke deposition in the reforming zone. EGR dilution preserves catalyst from overheating while minimizing the risk of coke deposition.